Analisis Korelasi Gula Darah Puasa, HbA1c, dan Karakteristik Partisipan - Nidaul Hasanah; Zullies Ikawati, Apt. (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2021)
Hemoglobin A1c (HbA1c) measurement is recommended as the gold standard in long-term blood sugar monitoring the diabetes patients because the fasting blood sugar (FBG) pattern alone cannot provide accurate information regarding the blood sugar variability true picture in type 2 Diabetes mellitus (T2DM) patients. However, many patients have limited access to HbA1c testing for financial reasons. It is necessary to know the relationship between HbA1c and GDP, and the factors that influence it, especially the research participant characteristics. This analytic observational study with a cross-sectional design involved 100 participants from T2DM patients in the hospital, outpatient clinics, and communities in Yogyakarta Province from January-May 2020. The HbA1c and FPG measurement was carried out using capillary blood samples by the research team. Characteristic data were obtained through direct interviews with participants, then analyzed using SPSS version 25 for windows, using the chi-square, Kolmogorov-Smirnov, and Spearman's rho test. The results showed that FPG was significantly positively correlated with HbA1c with moderate correlation criteria (r=0.74, P-value<0.0001). FPG showed a significant negative correlation to the glucometer ownership variable (r=-0.22, P-value= 0.04), and was independent of other parameters. Meanwhile, HbA1c significantly negatively correlated with age (r=-0.26, P-value=0.01), education level (r=-0.22, P-value=0.04), comorbidity (r=-0, 24, P-value=0.02), routine drug consumption (r=-0.29, P-value=0.01) and the ownership of glucometer (r=-0.26, P-value=0.01), but independent of gender, smoking status, daily menu, and physical exercise. It can be concluded that both GDP and HbA1c can be used as a reference for assessing glycemic status.